The Utilization Of Artificial Intelligence (AI) Technology In Learning: A Systematic Review - Dudin, Achmad (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This article examines the utilization of Artificial Intelligence (AI) technology in learning, focusing on six main aspects: adaptive learning personalization, real-time student performance analysis, interactive automated learning, language learning assistance, development of critical analytical skills, and enhancement of flexible learning resource availability. The study was conducted through a systematic review, synthesizing selected studies from 2013–2025, including UNESCO reports and implementations in Indonesia and other countries. Findings reveal that AI positions students at the center of the learning process, optimizing individual potential through instant feedback, innovative content such as chatbots and simulations, and early detection of learning issues. Although over 70% of global institutions have adopted AI since 2023, challenges like dependency, ethical usage, and reduced independence necessitate teacher supervision and responsible integration. These findings affirm that AI revolutionizes education to be more personalized, inclusive, and effective, with recommendations for teacher competency training to achieve optimal human-machine collaboration.